Cytotoxic effect of Kaempferia parviflora extract on normal oral keratinocytes and a human squamous carcinoma cell line - Thairat, Sarut; Srichan, Ratchaporn; Mala, Supaporn (Mahidol Dental Journal, 2022)
Objective: The purpose of this study was to investigate the cytotoxic effect of K. parviflora extract on normal oral keratinocytes (NOK) and a human squamous carcinoma cell line (HSC-4). Materials and Methods: The cytotoxic effect of ethanolic extract of K. parviflora root (0.46, 0.93, 1.87, 3.75, 7.5, 15, and 30 mg/ml) on normal oral keratinocytes and a human squamous carcinoma cell line was evaluated using an MTT assay per ISO 10993-5/2009. Results: The results revealed that after exposure to 0.46, 0.93, 1.87, 3.75, and 7.5 mg/ml K. parviflora extract NOK cell viability was 113%, 99%, 96%, 91%, and 75%, respectively, whereas 15 mg/ml and 30 mg/ml K. parviflora root treatment decreased cell viability to 15–31%. In HSC-4 cells, no cytotoxicity was demonstrated at concentrations ≤ 30 mg/ml. Conclusion: K. parviflora extract at concentrations ≤ 7.5 mg/ml was not cytotoxic to NOKs, and concentrations from 0.46–30 mg/ml were not cytotoxic to HSC-4 cells. This study provides additional basic knowledge concerning the biological response of NOK and HSC-4 cells to K. parviflora extract.